(untitled) (Research, Society and Development, 2021)
Contagion by the SARS-CoV-2 virus is one of the most recent diseases explained in medical sciences, since the initial reports, this virus has brought great concern due to its rapid transmission and dissemination, coinciding with the worsening of symptoms, such as fever, cough, fatigue, dyspnoea, headache, dizziness, diarrhea and vomiting. When referring to health, a quality of life includes satisfaction and well-being according to the patient’s conception, and this quality of life is affected by diseases and future consequences. The aim of the current study was on the impact of Covid-19 on the quality of life and health of patients after illness. This is a systematic review with a qualitative approach, which was based on a scientific literary survey, which led to an analysis, identification and description of the study. The study shows that Covid-19 causes changes in the quality of life and health of patients in different ways, depending on the severity of the disease, the complications caused by Covid-19, how the patient was hospitalized, and also their own characteristics which can cause the severity of the disease. It is concluded that Covid-19 has an impact on the quality of life of patients after the disease, leading to a significant deterioration in physical and mental health that can persist for months.